Effects of Parental Autonomy Support and Teacher Support on Middle School Students’ Homework Effort: Homework Autonomous Motivation as Mediator - Feng, Xiaowei; Xie, Ke; Gong, Shaoying; Gao, Lei; Cao, Yang (Frontiers in Psychology, 2019)
Abstract The present study tested whether students’ self-motivation mediated the association between adult support (parents’ support for autonomy, teacher support) and students’ homework effort. A sample of 666 Chinese middle school students was recruited to complete the parental autonomy support questionnaire, teacher support questionnaire, homework autonomous motivation questionnaire and homework effort questionnaire. Structural equation modeling showed that both parental autonomy support and teacher support positively predicted mathematics homework effort, and mathematics homework autonomous motivation was a mediator in these associations. The present study reveals the importance of adult support and autonomous motivation, and has theoretical and practical implications.